CONCEPTUAL APPROACHES TO ANALYSIS AND ASSESSMENT OF REGIONAL SOCIO-ECONOMIC SYSTEMS DEVELOPMENT RISKS - Pozmogov, Anatoliy; Kallagov, Boris; Btemirova, Rita (Revista Inclusiones, 2020)
The regional nature of Russian economy makes it necessary to study and comprehensively assesses regional socio-economic systems development risks. Regional socio-economic systems develop in different ways, thus giving rise to a sufficient number of factors which have a negative impact on conducting adequate assessment of territories’ socio-economic development level. The article objective is to clarify the concept of economic category "risk" and study complex approaches to system analysis and assessment of regional socio-economic system development risks and threats. The research results present classification of risks and threats to regional socio-economic systems development based on totality of characteristics and identifies two basic approaches to studying a set of socio-economic risks. A selective method for risk analysis is presented within the framework of the first approach and negative factors impact on risks is determined. Integral risk-determining factors for specific types of risks were identified within the framework of the second approach, in so doing, complex impact of such factors on other groups of risks associated with them was not identified.